Active vibration control of Flexible Joint Manipulator using Input Shaping and Adaptive Parameter Auto Disturbance Rejection Controller. (17th February 2016) - Li, W.P.; Luo, B.; Huang, H.
Abstract: This paper presents a vibration control strategy for a two-link Flexible Joint Manipulator (FJM) with a Hexapod Active Manipulator (HAM). A dynamic model of the multi-body, rigid–flexible system composed of an FJM, a HAM and a spacecraft was built. A hybrid controller was proposed by combining the Input Shaping (IS) technique with an Adaptive-Parameter Auto Disturbance Rejection Controller (APADRC). The controller was used to suppress the vibration caused by external disturbances and input motions. Parameters of the APADRC were adaptively adjusted to ensure the characteristic of the closed loop system to be a given reference system, even if the configuration of the manipulator significantly changes during motion. Because precise parameters of the flexible manipulator are not required in the IS system, the operation of the controller was sufficiently robust to accommodate uncertainties in system parameters. Simulations results verified the effectiveness of the HAM scheme and controller in the vibration suppression of FJM during operation. Highlights: FJM׳s hybrid controller with IS and APADRC is proposed. By APADRC, closed loop system of FJM will be consistent with a reference system, even if the configuration of FJM is changed. Hybrid controller design is simplified by using the HAM as well as increases the FJM׳s vibration control capability.